Exploration of the Optimal Desmopressin Treatment in Children With Monosymptomatic Nocturnal Enuresis: Evidence From a Chinese Cohort - Liu, Jiaojiao; Ni, Jiajia; Miao, Qianfan; Wang, Chunyan; Lin, Fang; Cao, Qi; Guo, Wei; Yang, Xue; Ji, Xiaolu; Zhai, Yihui; Bi, Yunli; Shen, Qian; et al. (Frontiers in Pediatrics, 2021)
Objectives: Nocturnal enuresis (NE) is a common pediatric condition, and desmopressin (dDAVP) is a first-line therapy for NE. The standard initial dosage of dDAVP is 0. 2 mg/day, and most guidelines recommend that the dose should be increased at 0.2 mg increments until dryness is achieved or to the maximal recommended dose. However, previous evidence has shown that this strategy seems insufficient to further improve efficacy and results in unnecessarily high doses for some patients. Our study aimed to assess the efficacy of our modified dDAVP treatment regimen in children with MNE in China and evaluate predictive factors associated with the dDAVP response. Methods: All MNE patients at the Department of Nephrology at Children's Hospital of Fudan University from January to December 2019 were prospectively and consecutively enrolled. dDAVP treatment comprised a dose titration period and a 3-month maintenance period. The efficacy of dDAVP was assessed according to the latest International Children's Continence Society criteria at the end of the study. Predictive factors were evaluated by logistic regression analysis. Results: Overall, 322 MNE patients were enrolled in our study, and 225 (69.9%) completed the study. The intention to treat analysis showed that the overall dDAVP response rate was 69.9%: among these patients 32.3% were complete responders, and 37.6% were partial responders. At the end of the study, 194/225 (86.2%) patients received a final dose of 0.2 mg, 24/225 (10.7%) patients received a final dose of 0.3 mg, and 7/225 (3.1%) patients received a final dose of 0.4 mg. Multivariate analysis showed that patients requiring lower doses to achieve responses were significantly more likely to experience complete response during the maintenance period [odds ratio (OR)=9.683; 95% confidence interval (CI), 2.770–33.846]. Conclusions: Our results indicate that the dDAVP treatment regimen provides a comparable efficacy to the international conventional treatment regimen with a lower overall dose. Low-dose responders were likely to achieve a complete response without increasing the dose; in these cases, the maximum dose might not be necessary.